(untitled) (Clinics, 2016)
OBJECTIVE: The aim of this study was to determine the efficacy of 252Californium neutron intracavitary brachytherapy using a two-channel Y applicator combined with external beam radiotherapy for the treatment of endometrial cancer. METHODS: Thirty-one patients with stage I-III endometrial cancer were recruited for this study. The stage I patients received only 252Californium neutron intracavitary brachytherapy with a two-channel applicator. The stage II and III patients received both 252Californium neutron intracavitary brachytherapy using a two-channel applicator and parallel-opposed whole pelvic radiotherapy. RESULTS: The five-year local control rate was 80.6% (25/31), the overall survival rate was 51.6% (16/31), and the disease-free survival rate was 54.8% (17/31). The incidence of serious late complications was 12.9% (4/31). CONCLUSIONS: 252Californium neutron intracavitary brachytherapy using a two-channel applicator combined with external beam radiotherapy was effective for treating endometrial cancer and the incidence of serious late complications related to this combination was within an acceptable range.